Human Papillomavirus prevalence among women with cervical intraepithelial neoplasia III and invasive cervical cancer from Goiânia, Brazil - Santos, Silvia Helena Rabelo dos (2003)
This study estimated the prevalence and distribution of human papillomavirus (HPV) types among women with cervical intraepithelial neoplasia (CIN) grade III and invasive cervical cancer from Goiás (Brazil Central Region). Seventy-four cases were analyzed and consisted of 18 CIN III, 48 squamous cell carcinomas, 4 adenocarcinomas, 1 adenosquamous carcinoma and 3 undifferentiated carcinomas. HPV-DNA sequences were examined in formalinfixed and paraffin-embedded tissues using primers from L1 region GP5+/GP6+. Polymerase chain reaction products were typed with dot blot hybridization using probes for HPV 16, 18, 31, 33, 45, 54, 6/11, 42/43/44, 51/52, 56/ 58. The prevalence of HPV was estimated to be 76% (56/74). HPV 16 was the most frequently found type, followed by HPV 33, 18 and 31. The prevalence of untyped HPV was 6%; 79% percent of the squamous cell carcinoma cases and 61% percent of the CIN III were positive for HPV and the prevalence rate of HPV types was the same for the total number of cases. According to other studies, HPV type 16 is the most prevalent virus in all Brazilian regions, but there is variation regarding to other types. Type 18 is the second most prevalent HPV in North, Southeast and South Brazil regions and types 31 and 33 are the second most prevalent HPV in Northeast and Central Brazil, respectively.